PENINGKATAN KEMAMPUAN MEMBACA NYARING CERITA PENDEK MELALUI PENERAPAN MODEL PROJECT BASED LEARNING PADA SISWA KELAS II UPTD SDN 1 BONIPOI - Elda Yewangu; Markus Sampe; Adam Bol Nifu Benu (STKIP Subang, 2026)
This study was motivated by the low ability of second-grade students at UPTD SDN 1 Bonipoi to read short stories aloud, as indicated by mispronunciations, inaccurate intonation, and a lack of expressive reading corresponding to story content. The research aimed to improve students’ ability to read short stories aloud through the application of the Project Based Learning (PjBL) model. This study employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of the stages of planning, implementation, observation, and reflection. The subjects were 21 students, comprising 11 boys and 10 girls. Data collection techniques included observation of teacher and student activities and a reading-aloud test. The data were analyzed qualitatively and descriptively to identify improvements in students’ reading performance. The findings revealed that the implementation of the Project Based Learning model significantly improved students’ reading-aloud abilities. In the first cycle, the average score increased from 63.4 (pre-action) to 72.1, though some students were still hesitant and lacked confidence in expressing the story’s meaning. In the second cycle, a more substantial improvement was observed, with the average score rising to 84.7 and 95,23% of students achieving the Minimum Mastery Criteria (KKM). Additionally, both teacher and student activities improved consistently from the “fair” to the “excellent” category. Therefore, the application of the Project Based Learning model proved effective in enhancing students’ ability to read short stories aloud, making learning more engaging, active, and meaningful in the elementary school context.